Lamotrigine in the treatment of bipolar disorder. - Bhagwagar, Z; Goodwin, G (2005)
Lamotrigine is a novel anticonvulsant agent that has recently been introduced as a long-term treatment in bipolar disorder. Its role in the treatment of epilepsy is based on its actions to decrease ion channel conductance and antagonise glutamatergic function. Therefore, it has a mode of action unlike other agents used on a long-term basis in mood disorders. The evidence for efficacy is stronger for the prevention of depressive, rather than manic, episodes. The pivotal trials are in bipolar I disorder, but there is interest in its actions in patients with bipolar II and spectrum conditions. Its efficacy in other psychiatric conditions remains to be properly established. It is well tolerated and, with careful prescribing, the incidence of rash occurs no more than with placebo; however this is still a concern. Although usually well tolerated, headache, insomnia and drowsiness are probably the most common side effects.